Gambaran Hematologi dan Tingkat Kelangsungan Hidup Ikan Jelawat (Leptobarbus hoevenii) dengan Penambahan Sinbiotik dalam Pakan - Nur Habibah; Agustina Agustina; Adi Susanto (Faculty of Science and Technology University Ibrahimy, 2026)
This study aims to determine the effect of administering synbiotic pectin from mandarin orange peel (PKJM) and Lactobacillus plantarum bacteria on the health of the hoven’s carp (Leptobarbus hoevenii) through hematological parameters and survival rates. The method used was a Completely Randomized Design with four treatments and three replications. The treatment consisted of different doses of PKJM combined with L. plantarum bacteria at a concentration of 108 CFU/mL of 0.1 mL/g, namely P0 (without synbiotic), P1 (5 g/kg PKJM), P2 (10 g/kg PKJM), and P3 (15 g/kg PKJM) in the feed. Hoven’s carp with a size of 8–9 cm were kept in containers for 30 days with 10 fish stocking per container and fed at-satiation with a frequency of 2 times a day in the morning and evening. Observations of hematological parameters consisting of hematocrit, hemoglobin, total erythrocytes and leukocytes were carried out on days 0 and 30, while the survival rate was observed for 30 days of fish maintenance. Data in the form of average values of hematological parameters and their increases, survival rates and water quality were analyzed descriptively in the form of tables and figures. The results of the study showed that the administration of synbiotics could increase the levels of hematological parameters. P2 with a dose of 10 g/kg PKJM + 0.1 mL/g L. plantarum was the best dose in increasing the hematological parameters of fish. The survival rate of hoven’s carp during the study was 96% in all treatments. In general, the results of this study indicate that the administration of synbiotics pectin from mandarin orange peel and L. plantarum bacteria can improve the health of hoven’s carp.